The hidden elephant: Modified abasic sites and their consequences - Yudkina, Anna V.; Zharkov, Dmitry O. (DNA repair, 2025)
Abasic, or apurinic/apyrimidinic sites (AP sites) are among the most abundant DNA lesions, appearing in DNA both through spontaneous base loss and as intermediates of base excision DNA repair. Natural aldehydic AP sites have been known for decades and their interaction with the cellular replication, transcription and repair machinery has been investigated in detail. Oxidized AP sites, produced by free radical attack on intact nucleotides, received much attention recently due to their ability to trap DNA repair enzymes and chromatin structural proteins such as histones. In the past few years, it became clear that the reactive nature of aldehydic and oxidized AP sites produces a variety of modifications, including AP site–protein and AP site–peptide cross-links, adducts with small molecules of metabolic or xenobiotic origin, and AP site-mediated interstrand DNA cross-links. The diverse chemical nature of these common-origin lesions is reflected in the wide range of their biological consequences. In this review, we summarize the data on the mechanisms of modified AP sites generation, their abundance, the ability to block DNA polymerases or cause nucleotide misincorporation, and the pathways of their repair. •Apurinic/apyrimidinic (AP) sites are abundant and highly reactive DNA lesions.•AP sites trap proteins on DNA; repair of such lesions is initiated by proteolysis.•AP site adducts are blocking for DNA polymerases and may be subject to BER.•AP sites form interstrand cross-links, also processed by BER DNA glycosylases.•New detection methods estimate the level of AP sites at 0.1–1 per 106 nucleotides.